Gender-based correlation profiles among the release factors and distance thrown in paralympic seated shot put - Lee, S.; Davis, R.; Judge, L. W.; Kwon, Y.-H.; Han, K.; Kim, Je.; Kim, Jaew.; Kim, Jaeh. (Adapted Physical Activity Quarterly, 2015)
The purpose of this study was to investigate the relationships among release factors (speed, height, and angle) and distance thrown in Paralympic seated shot put. Fortyeight trials performed by 11 men and 5 women during the 2012 US Paralympic trials in track and field were analyzed. With both genders combined, release speed (r = .95, p < .01) and angle (r = .51, p < .01) showed significant correlations to distance thrown. Release speed (r = .94, p < .01) in men and all release factors (r = .60-.98, p < .02) in women showed significant correlations to distance. Release speed and angle were identified as important predictors of the distance, explaining over 89-96% of the variance in distance thrown. Unlike athletes without disability, seated shot-putters exhibited significant positive speed-angle correlations (combined: r = .37, p < .01; women: r = .57, p = .03). Application of these results should address a focus in training on generating speed through the release point with a consistent release angle.